Direct Anterior Approach in Hip Hemiarthroplasty for Femoral Neck Fractures: Do Short-Term Outcomes Differ with Approach?: A Systematic Review and Meta-Analysis. Issue 9 (1st September 2022) - Khan, Irfan A.; Magnuson, Justin A.; Arshi, Armin; Krueger, Chad A.; Freedman, Kevin B.; Fillingham, Yale A.
Abstract : Background: Hip hemiarthroplasty (HA) is commonly used to treat femoral neck fractures, but it remains unclear if the surgical approach impacts patient outcomes for this commonly performed procedure. The objective of this systematic review and meta-analysis was to assess early postoperative outcomes in patients undergoing HA for femoral neck fracture with the direct anterior approach (DAA) compared with other approaches. Methods: The Cochrane Central Registry of Controlled Trials, MEDLINE, and Google Scholar databases were searched for randomized controlled trials, prospective nonrandomized trials, and retrospective studies published prior to September 7, 2021, comparing DAA with other approaches (anterolateral approach [ALA], direct lateral approach [DLA], and posterior-based approach [PA]) in HA for femoral neck fractures. This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Outcomes included functional outcomes, total complications, prosthetic dislocation, periprosthetic fracture, periprosthetic joint infection (PJI), reoperation, mortality, pain, operative time, and perioperative blood loss. Fixed effect odds ratios, along with their 95% confidence intervals, were used to analyze dichotomous variables. Significance was set at p < 0.05. Meta-analysis was conducted with Review Manager 5.4. Results: In total, 19 studies were included for qualitative analysis and 16 studies were included for quantitative analysis, with a total of 1, 604 cases analyzed (723 DAA, 215 ALA, 301 DLA, and 365 PA). Compared with other approaches, the use of the DAA for HA was associated with improved early postoperative functional outcomes, lower early postoperative pain scores, fewer total complications, and fewer prosthetic hip dislocations. The rates of periprosthetic fracture, PJI, and reoperation, pain scores beyond 40 days, operative time, perioperative blood loss, and mortality were not significantly different between surgical approaches. Conclusions: Utilizing the DAA while performing HA for femoral neck fractures is associated with improved functional outcomes, lower early postoperative pain scores, lower incidence of prosthetic hip dislocation, and potentially fewer total complications. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.